PEMBELAJARAN DAN PENILAIAN BERORIENTASI NILAI (AKHLAK) DAN DAMPAKNYA TERHADAP PERILAKU MAHASISWA STAIN PAMEKASAN - Moch. Muchlis Solichin (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2011)
Education represents the effort of systematic to bear quality grad of professional, for the reason must always innovate and reorientation at curriculum and study models so that it can face the challenge especially of the values friction at Islam and Indonesia of effect of culture and ideology contention of interracial and religion.Education model or formal in the form of study is claimed to orient at value (behavior). STAIN Pamekasan as education institution is claimed to emphasize behavior education as materialization of vision mission which tread on at islamic value and at Indonesia. This research is focused at how study and assessment which orient the value ( behavior) and how study impact and the assessment to student behavior. This research comes near with qualitative paradigm by means of compiler of interview data, observation and documentation to be analysed and interpreted in taking conclusion. Result of research is obtained, that is; there are some study model and assessment which orient the value (behavior), that is; to express the meaning from some theories, to connective the theoretical study with various value in life, to express the science benefit at subject constructed , explaining values implied in science area at the subject, explaining values implied in science area, practicing on behavior values.